2021
DOI: 10.1155/2021/7698030
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Schizophrenia: Etiology, Clinical, Pharmacological, and Treatment Implications

Abstract: Recent data suggests that the prevalence of smoking in schizophrenia remains high. While reports suggest that smoking increases the risk of developing schizophrenia, the potential causative role of smoking in this relationship needs further investigation. Smokers with schizophrenia are more likely to have more intense positive symptoms and lower cognitive function, but diminished intensity of extrapyramidal side effects than nonsmoking patients with schizophrenia. They were also more likely to exhibit aggressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 74 publications
0
22
0
2
Order By: Relevance
“…Tobacco consumption has been associated with higher levels of psychosis symptoms and lower cognitive function, 39 , 40 and greater smoking severity was a factor in increased premature mortality risk. 41 By contrast, tobacco cessation among people with psychosis has been associated with improved cognitive function and psychosis symptoms 42 , 43 and with reduced morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco consumption has been associated with higher levels of psychosis symptoms and lower cognitive function, 39 , 40 and greater smoking severity was a factor in increased premature mortality risk. 41 By contrast, tobacco cessation among people with psychosis has been associated with improved cognitive function and psychosis symptoms 42 , 43 and with reduced morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a previous randomized study has shown that nicotine replacement in smokers with schizophrenia was associated with lower levels of agitation 4 and 24 h after baseline (Allen et al, 2011). A recent review by Ding & Hu concluded that smokers diagnosed with schizophrenia displayed significantly more aggressive behavior than nonsmokers (Ding & Hu, 2021). Authors hypothesized that patients who smoke use cigarettes as “self‐medication” to alleviate their hostility problems and thus, have higher levels of baseline agitation and aggressiveness (Ding & Hu, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Ding & Hu concluded that smokers diagnosed with schizophrenia displayed significantly more aggressive behavior than nonsmokers (Ding & Hu, 2021). Authors hypothesized that patients who smoke use cigarettes as “self‐medication” to alleviate their hostility problems and thus, have higher levels of baseline agitation and aggressiveness (Ding & Hu, 2021). This hypothesis has also been raised in individuals without a history of mental illness (Bernstein et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although some data can be attributed to small and non-representative groups with regard to smoking prevalence, other studies with larger sample sizes produce different findings; For instance, data taken earlier by the National Comorbidity Survey (NCS) indicated that smoking prevalence in BD was 69%, whereas recent data from the National Health Interview Survey (NHIS) revealed a smoking rate of 46% [3]. Despite the difference in this prevalence depending on countries, clinical studies and populations have consistently indicated that the smoking prevalence is approximately two to three times higher in people with BD than in the general population [3,19,21]. However, higher smoking prevalence in people with bipolar disorder contributes to both early onset of smoking and a reduced success rate in smoking cessation.…”
Section: Prevalence Of Smoking In Mental Illnessmentioning
confidence: 99%